2017
DOI: 10.1177/1756287217724726
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in percutaneous nephrolithotomy: an internet-based survey

Abstract: Materials and methods Using Survey Monkey, a web-based survey (Supplementary Data; available online at www. surveymonkey.com) was created and administered via blast e-mails to members of the Endourological Society. The survey questionnaire covered demographic data, number of cases performed annually and details pertaining to technique of PCNL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…According to Ahmad et al, the use of retrograde intrarenal surgery (RIRS) in the Galdakao-modified supine Valdivia position has an increasing role in combination with PCNL in the contemporary management of staghorn stones. 34 , 35 In this survey, 24.5% preferred combined flexible ureteroscopy with PCNL (endoscopic combined intrarenal surgery, ECIRS) for complex staghorn stones. This trend is also reflected by 17.8% laparoscopic lithotomy for an impacted upper ureteric stone of ˃1.5cm.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…According to Ahmad et al, the use of retrograde intrarenal surgery (RIRS) in the Galdakao-modified supine Valdivia position has an increasing role in combination with PCNL in the contemporary management of staghorn stones. 34 , 35 In this survey, 24.5% preferred combined flexible ureteroscopy with PCNL (endoscopic combined intrarenal surgery, ECIRS) for complex staghorn stones. This trend is also reflected by 17.8% laparoscopic lithotomy for an impacted upper ureteric stone of ˃1.5cm.…”
Section: Discussionmentioning
confidence: 90%
“…In our survey average hospital stays of >3 days were reported by 130 (81.2%) of the PCNL practitioners, which contrasts with Ahmad’s study, in which 1–3 day average hospital stays were reported by 95.9% of PCNL practitioners. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive percutaneous nephrolithotomy (PCNL) has been widely used in the treatment of renal and upper ureteral calculi (1). Nephrostomy and double-J tubes are routinely placed after PCNL surgery, but the nephrostomy tube is associated with adverse events such as pain, channel infection, postoperative bleeding, and longer hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…However, a second-stage PCNL is commonly required for several reasons. Derived from an internet-based survey receiving 300 responses from Endourological Society members representing 47 countries, 14.3% of urologists preferred a second-stage PCNL to manage ≤1 cm stone residual following initial PCNL [ 1 ]. At many centers, second-look PCNL is routinely undertaken following initial, large stone burden PCNL to assure a complete stone clearance [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%